Revision of Taxigramma pseudaperta Séguy, 1941 and comparisons with sympatric T. multipunctata (Rondani, 1859) (Diptera: Sarcophagidae) - Richet, René; Verves, Yury G.; Whitmore, Daniel; Pape, Thomas (Zootaxa, 2013)
The identity of the nominal taxon Taxigramma pseudaperta Séguy, 1941 [type locality: France, Corse] is revised and an improved circumscription based partly on reared material of both sexes is presented through comparison with the very similar and sympatric species T. multipunctata (Rondani, 1859). A table is provided to separate first instars, puparia, males and females of these two taxa.